Different Benzendicarboxylate-Directed Structural Variations and Properties of Four New Porous Cd(II)-Pyridyl-Triazole Coordination Polymers - Zhao, Ying; Jing, Jin; Yan, Ning; Han, Min-Le; Yang, Guo-Ping; Ma, Lu-Fang (Frontiers in Chemistry, 2020)
Four new different porous crystalline Cd(II)-based coordination polymers (CPs), i. e., [Cd(mdpt)2]·2H2O (1), [Cd2(mdpt)2(m-bdc)(H2O)2] (2), [Cd(Hmdpt)(p-bdc)]·2H2O (3), and [Cd3(mdpt)2(bpdc)2]·2.5NMP (4), were obtained successfully by the assembly of Cd(II) ions and bitopic 3-(3-methyl-2-pyridyl)-5-(4-pyridyl)-1,2,4-triazole (Hmdpt) in the presence of various benzendicarboxylate ligands, i.e., 1,3/1,4-benzenedicarboxylic acid (m-H2bdc, p-H2bdc) and biphenyl-4,4′-bicarboxylate (H2bpdc). Herein, complex 1 is a porous 2-fold interpenetrated four-connected 3D NbO topological framework based on the mdpt− ligand; 2 reveals a two-dimensional (2D) hcb network. Interestingly, 3 presents a three-dimensional (3D) rare interpenetrated double-insertion supramolecular net via 2D ···ABAB··· layers and can be viewed as an fsh topological net, while complex 4 displays a 3D sqc117 framework. Then, the different gas sorption performances were carried out carefully for complexes 1 and 4, the results of which showed 4 has preferable sorption than that of 1 and can be the potential CO2 storage and separation material. Furthermore, the stability and luminescence of four complexes were performed carefully in the solid state.